2021
DOI: 10.1057/s41261-021-00165-1
|View full text |Cite
|
Sign up to set email alerts
|

Governance in the era of Blockchain technology in Qatar: a roadmap and a manual for Trade Finance

Abstract: Nations worldwide have sought to capitalize on the benefits of distributed ledger technology (DLT) including Blockchain, but struggled to strike a balance between encouraging investment and innovation in the technology while addressing the challenges and uncertainties through regulation. Through its FinTech (Financial Technology) Strategy, Qatar has sought to embrace DLT, but its regulatory approach also remains cautious. Trade Finance is an ideal business process to be disrupted through the benefits of DLT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Contrary to the position expressed by such authors as Ibrahim and Truby (2021), Takanashi (2020), Truby et al (2022), it has been proved that public institutions (factors of state regulation) can have a negative impact on blockchain finance: to retard their development even in a highly developed institutional environment. Thus, the increase in: guarantees of the rule of law, the level of economic freedom, the quality of government regulation and political and operational stability, instead of the expected support, hinders the development of blockchain finance.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Contrary to the position expressed by such authors as Ibrahim and Truby (2021), Takanashi (2020), Truby et al (2022), it has been proved that public institutions (factors of state regulation) can have a negative impact on blockchain finance: to retard their development even in a highly developed institutional environment. Thus, the increase in: guarantees of the rule of law, the level of economic freedom, the quality of government regulation and political and operational stability, instead of the expected support, hinders the development of blockchain finance.…”
Section: Discussionmentioning
confidence: 74%
“…RQ 3 : What influence do public institutions (factors of state regulation) have on blockchain finance as one of the key components of modern FinTech? In their publications Ibrahim and Truby (2021), Takanashi (2020), Truby et al (2022) indicate that strong public institutions and the favorable influence of government regulation factors (rule of law, economic freedom, high quality of government regulation, political and business stability, high level of development of the e-government system, as well as high efficiency of government regulation) have a positive (stimulating) impact on blockchain finance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is found that the public blockchain is vulnerable without an overseeing organisation [ 59 ]. Sandbox regulatory experiments should be conducted before launching the governance systems [ 153 ]. Apart from this, if DAO architectures are used to establish decision-making frameworks in public governance, it is recommended to have a coded rule to upgrade or change protocols when loopholes are identified [ 74 ].…”
Section: Thematic Analysismentioning
confidence: 99%
“…Another major legal tussle for using blockchain is the absence of a common currency system worldwide. If no currency is involved in the exchange, then there is no need for monetary regulatory approvals [ 153 ]. As of writing this paper, cryptocurrencies are bought using exchanged currency such as the dollar and rupee.…”
Section: Thematic Analysismentioning
confidence: 99%
“…This software established a decentralized and tamper-resistant ledger, which meticulously documents all transactions in a transparent and unchangeable fashion. The technology rapidly garnered attention among technology aficionados; nevertheless, its full capabilities were shown in 2016 when Wave, a financial technology firm, effectively conducted the inaugural trade finance transaction for a letter of credit utilizing blockchain (Ibrahim & Truby, 2022). This significant accomplishment represented a pivotal moment in the trajectory of global commerce, as it substantially diminished the duration of trade transactions from the customary span of 7-10 days to a mere 4 hours (Siddik et al, 2021).…”
Section: Introductionmentioning
confidence: 99%